Protective Effects of Coenzyme Q10 Along with Fe2O3 Nanoparticles On Sperm Parameters in Rats with Scrotal Hyperthermia: - Hashemi, Mehrdad; Deldar Abad Paskeh, Mahshid; Babaei, Nahid; Entezari, Maliheh; Doosti, Abbas (Galen Medical Journal, 2022)
Background: One of the most important factors in reducing the birth rate is male infertility, and one of the main reasons for male infertility is scrotal hyperthermia (SH). Therefore, this study aimed to investigate the protective effect of coenzyme Q10 (CoQ10) along with Fe2O3 nanoparticles on semen parameters in rats with SH. Materials and Methods: Forty-eight adult male Wistar rats were divided into eight groups: healthy control, control group receiving Fe2O3 nanoparticles, control group receiving CoQ10, control group receiving Fe2O3 nanoparticles plus CoQ10, SH group, SH group receiving CoQ10, SH group receiving Fe2O3 nanoparticle, and SH group receiving Fe2O3 nanoparticles plus CoQ10. After killing rats, semen was collected from epididymal tissue, and parameters such as sperm viability, motility, concentration, and morphology were studied. Results: SH significantly reduced sperm concentration, motility, and viability, as well as altering sperm morphology in rats. Nevertheless, CoQ10 strongly improved sperm parameters in SH rats. Fe2O3 nanoparticles led to a sharp decrease in sperm parameters; however, during the simultaneous administration of Fe2O3 nanoparticles with CoQ10, improvement in sperm parameters was seen in the SH rats. Conclusion: Our findings suggest that CoQ10, along with Fe2O3 nanoparticles, has a protective effect against spermatogenic cell death induced by SH. Thus, green synthesis of nanoparticles with the administration of antioxidants, including CoQ10 is recommended for the treatment of SH. [GMJ.2022;11:e2046]